IDENTITY AND COLLECTIVE ACTION – SYSTEM APPROACH - Polishchuk, Oleksandr; Polishchuk, Olena (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2023)
Introduction. The article examines the phenomenon of identity within the formation of collective action in societies with the “Between” status. This status is a condition for the formation of Homo, who is ready to survive and adapt to the imposed conditions. The aim determines the need for a comprehensive analysis of approaches to the phenomenon of identity in terms of the formation of collective action. This aimdetermines the epistemological and praxeological components of the formation of a new type of Homo. The tasks of the study are clarifying the essence of the main concepts within the selected problem, that are important in the process of becoming a person; defining the place of freedom as an opportunity to act; developing an interpretative scheme of collective action for the processes of creation of Homo through identity. Research methods. In order to study the issue in detail and justify the conclusions, the following methods were used: 1) general: comparison, analysis, synthesis, abstraction, and specification; 2) special: historical method, civilizational method, and behavioral. Research results. Considering the values, it has been demonstrated that a society whose collective action is aimed at development and life, using freedom, will choose the path of civilization and will fight for it. This is due to the human desire for life filled with dynamic change. Discussion. However, this is not the case with totalitarian societies. The role of historical memory and the collective unconscious within the mythologizing of consciousness has been identified. In particular, it has been demonstrated that the mythologizing of consciousness, and the lack of objective analysis of historical events have negative consequences for collective agents, based on the fact that they are active participants in the processes of state formation and history. Conclusions. The phenomenon of identity is examined in the article through the socio-political and socio-economic processes occurring in the country and in the world. After all, these processes are becoming the landmark of the globalized world, which determines the collective identity of the agent. The consequence of such certainty is the impact on reforming the entire social system.